Marketing Analysis for Hive’s Entry in China - ye, ran (2016)
In 2013, China is the second largest retail market globally and Asia’s largest by contributing $3.4 trillion towards consumer economy. It’s retail market has become one of the most lucrative and rapidly growing market in the world (Ku, 2016). After US, China had contributed the largest market size in terms of value for 241 categories (Biciunite, 2015). According to PWC (2015), China is expected to surpass the US and become the world’s largest retail market overall by 2018.